Cemented Versus Hybrid Technique of Fixation of the Stemmed Revision Total Knee Arthroplasty: A Literature Review. Issue 9 (1st May 2022) - Ayekoloye, Charles; Radi, Mehran; Backstein, David; Qa'oud, Moayad Abu
Abstract : Stems are required during revision total knee arthroplasty to bypass damaged periarticular bone and transfer stress to healthier diaphyseal bone. The mode of stem fixation, whether fully cemented or hybrid, remains controversial. Improvements in surgical technique and implant and instrument technology have improved our ability to deal with many of the challenges of revision total knee arthroplasty. Recent publications that reflect contemporary practice has prompted this review of literature covering the past 20 years to determine whether superiority of one fixation mode over the other can be demonstrated. We reviewed single studies of each type of fixation, studies directly comparing both types of fixation, systematic reviews, international registry data, and studies highlighting the pros and cons of each mode of stem fixation. Based on the available literature, we conclude that using both methods of fixation carries comparable outcomes with marginal superiority of the hybrid fixation method, which is of nonstatistical significance, although on an individual case basis, all fixation methods should be kept in mind and the appropriate method implemented when suitable.